A Structured End-of-Life Curriculum for Neonatal–Perinatal Postdoctoral Fellows. (May 2015) - Harris, Leslie L.; Placencia, Frank X.; Arnold, Jennifer L.; Minard, Charles G.; Harris, Toi B.; Haidet, Paul M.
Death in tertiary care neonatal intensive care units is a common occurrence. Despite recent advances in pediatric palliative education, evidence indicates that physicians are poorly prepared to care for dying infants and their families. Numerous organizations recommend increased training in palliative and end-of-life care for pediatric physicians. The purpose of this study is to develop a structured end-of-life curriculum for neonatal–perinatal postdoctoral fellows based on previously established principles and curricular guidelines on end-of-life care in the pediatric setting. Results demonstrate statistically significant curriculum effectiveness in increasing fellow knowledge regarding patient qualification for comfort care and withdrawal of support ( P = .03). Although not statistically significant, results suggest the curriculum may have improved fellows' knowledge of appropriate end-of-life medical management, comfort with addressing the family, and patient pain assessment and control.